THE IDEOLOGICAL HEGEMONY IN THE CONSTRUCTION OF MELAYU RIAU COMMUNITY CULTURAL IDENTITY ON THE ARCHITECTURE DESIGN - Nina Andriana (Widyariset, 2011)
This article explains the hegemony of ideology in the construction of local cultural identity on architectural design, found by using Roland Barthes’ semiotical analysis. The research is qualitative with descriptive design, colled from interpretation of the data using semiotics analysis and depth interview. In its conclusion, the writer suggested that architectural design as a cultural artifact should be formed as one of the objects in political communication researches, by using cultural studies approach which shows the hegemonic practice. The need of guidelines of local cultural architectural norms to strengthen local cultural identity in architectural forms as a cultural artifact, also important thing to local goverment concerned.